Analysis of Hyperpersonalized Marketing Strategy on Marketer Performance and Potential for CASA Improvement - Sevtiawan, Andry; Cahyagunarso, Aryo; Wibowo, Nurdi Dwianto (Journal Research of Social Science, Economics, and Management, 2026)
Increasing low-cost funds, or Current Account and Savings Accounts (CASA), has become a key focus for banks to optimize funding costs and increase profitability. In an increasingly digital era, banks can leverage big data analytics–based technology to develop more effective and efficient marketing strategies. This technology enables the processing of transaction data, digital interactions, and customer behavior to increase engagement and retention. This research aims to (1) analyze the implementation of hyperpersonalized marketing strategies in the banking sector; (2) examine the influence of data-based marketing strategies on marketer performance; and (3) analyze the potential for increasing CASA through data-based marketing strategies. This research uses a qualitative approach with a systematic literature review method to examine various studies related to digital marketing strategies in the banking sector. The results show that utilizing customer transaction data and digital interactions enables banks to conduct more accurate customer segmentation. This study examines hyperpersonalized marketing strategies based on data-driven technology that can improve marketer performance, as well as the potential for increasing CASA, by focusing on identifying marketer success factors in increasing engagement, the potential for increasing CASA, and the challenges in implementing this strategy, using literature analysis and case study methods.